Assessment the satisfaction level of faculty members from virtual teaching during corona crisis in Rafsanjan School of Medicine - Mitra Abbasifard; Hassan Ahmadinia; Alireza Moezi; Foad Iranmanesh; Maryam Shahabinejad; Hamid Ostadebrahimi; Fateme Heidari; Zahra Bagheri-Hosseinabadi; Mahsa Hassanipour (Journal of Education and Health Promotion, 2024)
BACKGROUND: Evaluating the experiences and the satisfaction level of the academic members is an important parameter in planning for virtual education during COVID-19 pandemic. The present study was designed to evaluate the satisfaction level of faculty members of Rafsanjan School of Medicine regarding virtual education in COVID-19 crisis in two stages between 2019 and 2022. MATERIAL AND METHODS: This descriptive study was conducted on the faculty members of Rafsanjan Medical School. The satisfaction level with virtual education during the COVID-19 pandemic was determined using a researcher-made questionnaire with appropriate validity and reliability. For analysing of quantitative variables, the Kolmogorov–Smirnov test, independent t tests and one-way analysis of variance and multiple linear regression were used. RESULTS: Data showed that only 15.2% of the faculty members had a previous experience of virtual teaching prior to the pandemic and 30.3% had a history of passing the empowerment course on virtual education before the COVID-19 crisis. Moreover, 68.2% passed the empowerment course on virtual education at the same time as the COVID-19 epidemic spread. The overall satisfaction with virtual education in the first and second stages of the study was 49.05 and 49.22 out of 100, respectively. The satisfaction of NAVID learning management system was 66.66 percent among faculty members. The level of satisfaction in non-clinical members was significantly more than clinical members. CONCLUSION: The overall satisfaction of faculty members with virtual education was at an average or medium level. From the point of view of the faculty members, some aspects of virtual education need to be improved. Therefore, it seems necessary to improve the infrastructure and empower the faculty members to enhance the quality of virtual education.